2002
DOI: 10.1073/pnas.122238899
|View full text |Cite
|
Sign up to set email alerts
|

ADP ribosylation of human neutrophil peptide-1 regulates its biological properties

Abstract: In human airways, epithelial cells lining the lumen and intraluminal cells (e.g., polymorphonuclear cells) participate in the innate immune response. These cells secrete or express on their surfaces arginine-specific ADP ribosyltransferases. Defensins, antimicrobial proteins secreted by immune cells, are arginine-rich, leading us to hypothesize that ADP ribosylation could modify their biological activities. We found that an arginine-specific ADP ribosyltransferase-1 present on airway epithelial cells modifies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 35 publications
4
109
1
Order By: Relevance
“…The latter are due to glycosylphosphatidylinositol-anchored or secreted enzymes that can modify either soluble or plasma-membrane-associated protein targets, including the P 2 X 7 purinergic receptor, human neutrophil protein 1, and ␣ 7 integrin (13)(14)(15). Intracellular, enzymatic mono-ADPribosylation modifies proteins with roles in cell signaling and metabolism, such as the chaperone GRP78/BiP, the ␤ subunit of the heterotrimeric G proteins, and mitochondrial glutamate dehydrogenase (GDH) (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The latter are due to glycosylphosphatidylinositol-anchored or secreted enzymes that can modify either soluble or plasma-membrane-associated protein targets, including the P 2 X 7 purinergic receptor, human neutrophil protein 1, and ␣ 7 integrin (13)(14)(15). Intracellular, enzymatic mono-ADPribosylation modifies proteins with roles in cell signaling and metabolism, such as the chaperone GRP78/BiP, the ␤ subunit of the heterotrimeric G proteins, and mitochondrial glutamate dehydrogenase (GDH) (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…HNP-1 was reduced, cleaved by trypsin, and analyzed by reverse-phase chromatography/mass spectrometry as described (17,18), except that the reverse-phase column was a Zorbax 300SB-C18, 2.1 ϫ 50 mm 3.5 m, and the mass spectrometer was an Agilent model G1969 (Agilent Technologies) with a time-of-flight detector. Mass spectra were deconvoluted with the Agilent software, MassHunter version 2, and the fraction of each species was calculated from the areas of the deconvoluted peaks.…”
Section: Methodsmentioning
confidence: 99%
“…After ADP-ribosylation by ART1, HNP-1 had reduced antimicrobial and cytotoxic activities but maintained its ability to recruit T lymphocytes and release IL-8 from A549 cells (17). To understand the cationicity of defensins, 3 of 4 arginines in HNP-1 (not arginine 5) were replaced with lysine or ornithine (9).…”
Section: Nmol) (D and E)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also shown that ART1, which is constitutively expressed on the surface of cells lining the airway lumen [23], modifies defensin human neutrophil peptide-1 (HNP-1), an antimicrobial peptide released by neutrophils. Indeed, ADP-ribosylation by ART1 and not other mART decreased antimicrobial and cytotoxic activities of HNP-1 but not the ability to stimulate T cell chemotaxis and interleukin-8 (IL-8) release from lung epithelial cells [26]. Moreover ADP-ribosylated HNP-1 was identified in bronchoalveolar lavage fluid (BALF) from patients with asthma, idiopathic pulmonary fibrosis, or a history of smoking but not in normal volunteers [27].…”
Section: Art1mentioning
confidence: 99%